Hemopericardium and Cardiac Tamponade Secondary to Migrated Inferior Vena Cava Filter. (21st November 2018) - Mehta, Jeet J.; DeMarco, Benjamin; Vavalle, John P.; Tahir, Khola S.; Rossi, Joseph S.
Abstract : A 73-year-old female presented with cardiogenic shock secondary to hemopericardium and cardiac tamponade. Imaging revealed two fractured legs of an inferior vena cava filter, with one leg within the anterior myocardium of the right ventricle and another penetrating the inferior septum through the middle cardiac vein. Hemopericardium and cardiac tamponade were treated with pericardiocentesis. A multidisciplinary meeting resulted in deferring further action against the embedded fractured legs of the filter with consideration of the patient's age and comorbidities. This case report should alert clinicians to think about hemopericardium as a cause of cardiac tamponade and cardiogenic shock in a patient with a history of an inferior vena cava filter placement.